2019
DOI: 10.4022/jafib.2195
|View full text |Cite
|
Sign up to set email alerts
|

Cardiothoracic Surgery Residency Training in Surgical Ablation for Atrial Fibrillation

Abstract: Background : As no standardized curriculum exists for training cardiothoracic surgery residents in surgical ablation for atrial fibrillation, there is potential for variation in operative technique, patient selection, and overall application. Thus we sought to assess the exposure of current residents in order to identify areas for improvement in their education. Methods : A survey was emailed to residents inquiring about their training experience in surgical ablation for atrial fibrillation. Residents were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Exposure to complete ablations and familiarization with the anatomic boundaries may be accomplished in the way of simulation, tissue labs, or higher-fidelity models ( 16 ). In the case herein, the 3D printing model enabled a dynamic visualization of the spatial relationship between the specific ablation lines and the critical anatomic references such as the coronary sinus, the mitral isthmus, the posterior mitral annulus, and the right coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to complete ablations and familiarization with the anatomic boundaries may be accomplished in the way of simulation, tissue labs, or higher-fidelity models ( 16 ). In the case herein, the 3D printing model enabled a dynamic visualization of the spatial relationship between the specific ablation lines and the critical anatomic references such as the coronary sinus, the mitral isthmus, the posterior mitral annulus, and the right coronary artery.…”
Section: Discussionmentioning
confidence: 99%
“…examined cardiothoracic surgery resident aptitude with the Cox-Maze surgery. 11 The study revealed a significant lack of perceived competence and training. Trainees on average ranked a 3 out of 5 (Likert scale) for "satisfaction with surgical ablation training," and 2 out of 5 for "satisfaction with Cox-Maze IV.…”
Section: Introductionmentioning
confidence: 93%
“…Also, even though I mentioned that recent graduating cardiothoracic surgeons are more facile with thoracoscopic techniques, it is equally important to mention that unfortunately most junior attendings are not comfortable with surgical ablation. A recent study from Dr. DeBoard et al examined cardiothoracic surgery resident aptitude with the Cox‐Maze surgery 11 . The study revealed a significant lack of perceived competence and training.…”
Section: Convergent Proceduresmentioning
confidence: 99%